PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DAN MOTIVASI BELAJAR PESERTA DIDIK KELAS VIII B SMP NEGERI 3 PONOROGO (Universitas PGRI Sumatera Barat, 2018)
This study aims to: (1) describe the implementation of mathematics learning using a cooperative learning model type think pair share to improve understanding of mathematical concept and learning motivation of student, (2) describe the results of an increase in concept understanding and learning motivation of students in class VIII B of SMP Negeri 3 Ponorogo through cooperative learning model type think pair share. This research is a classroom action research (CAR) with data sources include all students of class VIII B consist of 30 students. This study was conducted in two cycles with each cycle includes four phases: planning, implementation, monitoring/ observation, reflection. The results showed that: (1) the learning process using cooperative learning model TPS in the second cycle has been entered in the excellent category; (2) indicator of the ability to understand mathematical concepts in the second cycle, all indicators have reached very good categories; (3) learning motivation of students in the second cycle reached a score of 67,75% include in the high category. Thus, it can be concluded that the study with cooperative learning model of think pair share the type can improve the understanding of mathematical concepts and motivation of students in class VIII B of SMP Negeri 3 Ponorogo.